ORAL BLEEDING AS A SOLE PRESENTATION OF IDIOPATHIC THROMBOCYTOPENIC PURPURA IN AN ELDERLY MAN - Yousif, Mogahid Abdelrahman; Elawad, Ali Mohamed Ahmed (Gezira Journal of Health Sciences, 2010)
In this article we present a case of ITP in an elderly man presented to a dental clinic with only oral bleeding. . (ITP) is the most common acquired bleeding disorder occurring in previously healthy children and other different ages. . Clinically, ITP presents with petechiae, ecchymoses, haematomas, epistaxis, haematuria, mucocutaneous bleeding, and occasionally, haemorrhage into tissues. It is unusual for ITP to have a sole oral presentation .The patient  referred to our dental clinic as oral heamongiomic patient,complaint of mouth bleeding  and multiple heamatomas in the lower lip, tongue , palate and floor of the mouth.The patient improved rapidly after predinsolone as total oral treatment.The investigations and treatments are described